1994
DOI: 10.1002/elps.11501501164
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a single base mismatch in double‐stranded DNA by electrophoresis on uncrosslinked polyacrylamide gel

Abstract: Uncrosslinked polyacrylamide forms gels in the concentration range of 15-40% acrylamide. Electrophoresis in these gels of a commercially available 350 bp heteroduplex DNA preparation separates it from the homoduplex DNA of the same size. The separation is qualitatively equivalent to that previously achieved in a commercial proprietary gel ("Mutation Detection Gel" of AT-Biochem), or in an equivalent 14% T, 0.15% C (N,N'-methylenebisacrylamide) gel, but the mechanical stability of mutation detection electrophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Indeed in the crystal structures of oligonucleotides containing a wobble base pair, base stacking in the neighborhood of the mismatch is perturbed and helical parameters are altered [39]. NMR studies find that a G/T mismatch causes local flexibility [42], and electrophoresis using uncrosslinked polyacrylamide gel revealed that DNA with a single mismatch migrates differently from normal DNA and resembles kinked species [43].…”
Section: Base Unstacking Is a Common Feature In Repair Protein-dna Comentioning
confidence: 99%
“…Indeed in the crystal structures of oligonucleotides containing a wobble base pair, base stacking in the neighborhood of the mismatch is perturbed and helical parameters are altered [39]. NMR studies find that a G/T mismatch causes local flexibility [42], and electrophoresis using uncrosslinked polyacrylamide gel revealed that DNA with a single mismatch migrates differently from normal DNA and resembles kinked species [43].…”
Section: Base Unstacking Is a Common Feature In Repair Protein-dna Comentioning
confidence: 99%
“…The physical basis for the altered electrophoretic mobility is presumably the difference in the extent of DNA bending (Ganguly et al . 1993;Pulyaeva et al . 1994)…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we have directly verified that different mobilities of various homoduplex fragments can arise from single nucleotide substitutions (Figures 1a and 2c,d). The physical basis for the altered electrophoretic mobility is presumably the difference in the extent of DNA bending (Ganguly et al, 1993;Pulyaeva et al, 1994) © Blackwell Science Ltd, The Plant Journal, (1998), 16, 117-125 Application of duplex analysis markers Analysis of CAPS markers. Gene mapping and positional cloning in Arabidopsis thaliana benefited tremendously from the development of CAPS markers (Konieczny and Ausubel, 1993).…”
Section: Migration Behaviour On High Resolution Gelsmentioning
confidence: 99%
“…Precisely how the unpaired bases are involved is not yet clear. They may contribute simply by the helical distortion (30,31) or flexibility they induce, causing an unfavorable milieu for the DNA replication machinery. These sites may also be tagged by protein…”
Section: Role Of Stem-loop Structures In Mutagenesismentioning
confidence: 99%